Innovation of Areca catechu Compounds Combined with Fluoxetine as Antidepressant by In Silico Method - Riryn Novianty; Rexi Dwi Wardana; Ulya Putri Ningsih; Rahmad Setiawan Rabb (LPPM Universitas Muhammadiyah Riau, 2023)
Depression is a mental illness that has become a common problem worldwide with more than 300 million cases. The study aimed to determine the effectiveness of natural compound modification with synthetic compounds as new antidepressant drug candidates. The method used in the research is In Silico approach using ChemSketch software, BIOVIA Discovery Studio Visualizer (DSV), and Autodock Vina. The bond-free energy result from a combination of arecoline, homoarecoline and guvacoline with fluoxetine on 2Z5Y protein were -7.1 kcal/mol; -7.1 kcal/mol and -7.6 kcal/mol, respectively. Meanwhile, in 2NW8 protein, the bond free energy observed were -6.3 kcal/mol; -6.3 kcal/mol, and -8.8 kcal/mol, respectively. Based on bond-free energy data, the additive interaction of arecoline-fluoxetine and fluoxetine-homoarecoline on MAO-A protein (2Z5Y) was barely different from fluoxetine itself. Meanwhile, the additive interaction of guvacoline-fluoxetine was better with serotonin precursor protein (2NW8) rather than MAO-A protein (2Z5Y).